THE ROLE OF ANALYTICAL AND VISUALIZATION DATA TO OPTIMIZE ONLINE SALES - Triana, Yaya Sudarya; Kaburuan, Emil Robert; Rahmad, Khozaeni Bin; Jumaryadi, Yuwan (Universitas Mercu Buana, 2025)
In the digital era, data analytics is a key factor in increasing sales and competitiveness for individuals, companies, industries or governments. The use of data analytics allows us to understand market trends, customer behavior, and develop more effective marketing strategies. Studies show that companies that implement data analytics experience significant increases in revenue and better operational efficiency. The purpose of this article is to review how analytics can be used to understand audience behavior and preferences, and how this information can be used to target the right consumers with more relevant messages. By using sophisticated analytics tools, companies can gain insights from customer data, from purchasing patterns to interactions with digital platforms, enabling more informed and accurate decision making. Through a data-driven approach, companies can provide more personalized services and increase customer satisfaction. The implementation of data analytics also allows businesses to respond to market changes more quickly and precisely. With proper implementation, data analytics is not only a decision support tool, but also a key strategy in business growth. Therefore, investment in analytics technology is essential to ensure the sustainability and competitiveness of companies in the long term. In the data analytics process, there are 4 stages, namely Data collection, Data processing, Data analysis, and Data interpretation. Companies can gain competitive advantage by optimizing operations, increasing efficiency, responding to market changes, and predicting future trends through this process. Data analytics changes the way businesses operate by helping to understand customers, find opportunities, and make evidence-based decisions. It also improves operational efficiency and risk management, supporting innovation and long-term growth. The output targets of this activity are publications in international/national journals/Proceedings, IPR/HKI and publications on social media.